Lebanese elementary mathematics teachers' conceptions of formative assessment and of its uses in the classroom - Abi Faraj, Nadine Hassan (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2011)
The study investigated and compared (a) the conception that Lebanese pre-service and in-service elementary mathematics teachers hold about formative classroom assessment, (b) the formative assessment practices that Lebanese pre-service and in-service elementary mathematics teachers follow, and (c) the tools that pre-service and in-service teachers adopt in their practice during mathematics classroom formative assessment. A sample of 105 pre-service and in-service teachers completed a questionnaire titled Lebanese teachers Conceptions of Formative Assessment and their Uses in Classrooms, that was designed by the researcher to explore the conceptions that teachers hold about formative assessment, its practices, and tools. A sample of 24 teachers (12 in-service and 12 pre-service) was chosen to participate in structured interviews that followed the questionnaires. The responses of the participants in the questionnaire and interviews were analyzed based on Brown s model of assessment (Brown, 2005), and according to the Qualification and Curriculum Authority (QCA) components of practices of formative assessment (McCallum, 2000). Accountability and ranking conceptions of formative assessment dominated teachers pedagogical conceptions of formative assessment. The results of the study revealed that teachers conceive that formative assessment should be used to check students mathematical understanding in class (pedagogical conceptions) in order to provide them with needed feedback through the use of grades (accountability conceptions of formative assessment). Moreover, they conceive the importance of formative assessment in categorizing students and providing schools with data on their students performance. With regard to teachers practices of formative assessment, teachers subscribe partially to the involvement of students in their learning and modeling quality as practices of formative assessment. However, they did not seem to subscribe to the use of giving feedback and self -assessment as practices of formative assessment. While with regard to formative assessment tools, teachers mostly reported the use of formative assessment tools that provide them with direct feedback about their students mathematical performance. They seemed to adhere to the use of tools that can be easily graded and can be easily used to identify the acquired skills and the skills that need to be developed by the learner. However, Teachers seemed to shy away from using formative assessment tools that require classroom time and follow-up after students performance. Moreover, they did not report the use of formative assessment tools that involve students in the process of formative assessment. Pre-service and in-service teachers did not differ in their conceptions of formative assessment. However, they differed in some of their practices of formative assessment. In-service teachers reported less usage than pre-service teachers of some of the formative assessment practices, although, in-service teachers have more experience than pre-service teachers in the use of assessment in the classroom, pre-service teachers were more inclined to the use of different practices of formative assessment. Thus either experience did not play a role in shaping teachers practices of formative assessment, or in-service teachers did not exploit these practices because they require time inside the classroom. Similarly, experience did not play role in shaping their use of different tools of formative assessment. Pre-service teachers reported more frequent usage of all the items except for teacher-made written tests. In-service teachers focused mostly on the formative assessment tools that provide them with direct feedback about their students performance since they are more practical to use in their classes.
: Mémoire
Keywords: Evaluation Scolaire; L enseignement du Maths; Les Attitudes et conceptions des enseignants; Math education School Evaluation; Teachers attitudes and conceptions